Hepatic Glucagon Signaling Regulates PCSK9 and LDL-Cholesterol - Spolitu, Stefano (Circ Res, 2019)
RATIONALE: Glucagon is a key hormone that regulates the adaptive metabolic responses to fasting. In addition to maintaining glucose homeostasis, glucagon participates in the regulation of cholesterol metabolism, however, the molecular pathways underlying this effect are incompletely understood. OBJECTIVE: We sought to determine the role of hepatic glucagon receptor (Gcgr) signaling in plasma cholesterol regulation and identify its underlying molecular mechanisms. METHODS AND RESULTS: We show that Gcgr signaling plays an essential role in low-density lipoprotein (LDL) cholesterol homeostasis through regulating the proprotein convertase subtilisin/kexin type 9 (PCSK9) levels. Silencing of hepatic Gcgr or inhibition of glucagon action increased hepatic and plasma PCSK9 and resulted in lower LDL receptor protein and increased plasma LDL-cholesterol. Conversely, treatment of WT mice with glucagon lowered LDL-cholesterol levels, whereas this response was abrogated in Pcsk9(−/−) and Ldlr(−/−) mice. Our gain- and loss-of-function studies identified exchange protein activated by cAMP-2 (Epac2) and Ras-related protein-1 (Rap1) as the downstream mediators of glucagon’s action on PCSK9 homeostasis. Moreover, mechanistic studies revealed that glucagon affected the half-life of PCSK9 protein without changing the level of its mRNA, indicating that Gcgr signaling regulates PCSK9 degradation. CONCLUSIONS: These findings provide novel insights into the molecular interplay between hepatic glucagon signaling and lipid metabolism and describe a new post-transcriptional mechanism of PCSK9 regulation.